Corporate Communication Management (CCM) and organisational performance: A review of the current literature, conceptual model and research propositions - Mohamad, Bahtiar; Abu Bakar, Hassan; Halim, Haslina; Ismail, Ahmed Rageh (Elsevier Ltd., 2014)
Corporate communication received great attention from scholars and the business community more than 40 years ago due to changes in global business environments.Many scholars believe there are influences of corporate communication management (CCM) on organisational performance, yet there is a paucity of studies on the validation of this theoretical assumption.Therefore, the main purpose of this paper is to address the gap by providing an elevated understanding of CCM and its consequences. The managerial and policy implications provided in this study help corporate communication practitioners to identify the practical needs of their work and design an appropriate CCM programme.